Late Diagnosis of Extralobar Pulmonary Sequestration: Two Cases with an Uncommon Malformation - Evman, S.; Batirel, H. F.; Yüksel, M. (The Thoracic and Cardiovascular Surgeon, 2012)
Pulmonary sequestration is a congenital bronchopulmonary malformation, characterized by a mass of nonfunctioning lung tissue which receives its blood supply from a systemic artery. This increased blood flow and the inflammation in the sequestrated segments are positive on PET imaging, arousing the suspicion of malignancy. We report two cases of PET-positive extralobar sequestration that presented in patients of middle age and were successfully treated with surgical resection, indicating the role of surgery and the false-positive PET-CT appearance of sequestration cases.
Keywords: bronchopulmonary sequestration; positron emission tomography, PET; lung; benign or congenital lesions